Pembelajaran E-Commerce sebagai Sarana Pemasaran dan Penjualan Batik Songsong secara On Line di Desa Sewulan Kecamatan Dagangan Kabupaten Madiun - Hanafi, Rindyah (JURNAL DAYA-MAS, 2019)
Abstract—Indonesian Batik by UNESCO has been designated as Masterpieces of the Oral and Intangible Heritage of Humanity. since October 2, 2009. In each area batik craft is a regional superior product. At this time the development of batik began to be popular with all circles because it has characteristics, distinctive features and variety. Batik Songsong is a batik with distinctive features made by batik craftsmens in the village of Sewulan, Dagangan District, Madiun Regency. Mentoring for batik craftsmens was carried out from October to December 2018 in 6 (six) batik craftman  in the village of Sewulan. In general batik craftsmens do not understand the use of the internet to trade online so far how to market goods in conventional or offline ways. Batik craftsmen are taught learning online by using Facebook and Instagram social media applications. Batik Craftsmens were introduced and taught how to use Facebook and Instagram applications via smartphones and laptops to trade so that the produced batik Songsong produced were widely known and could achieve increased income. In order for the use of Facebook and Instagram applications to succeed, then batik crafmans need to be monitored continuously. Keywords—:  Characteristics, E-Commerce, Batik Songsong, Sewulan Village.